Coconut Oil as a Therapeutic agent in Medication Induced Contact Dermatitis - Dhondi, Sai Karthik; Puneem, Ushasree; Guttedar, Ashwini; Bommakanti, Kalpana; Sindgi, Vasudeva Murthy (Indian Journal of Pharmacy Practice)
Penile Candidiasis is said to be an infection of the penis caused by the yeasts from the genus Candida. Contact dermatitis is an intense or incessant skin inflammation brought about by cutaneous association with a substance, biologic, or physical agent. The location and shape of the rash provide important clues to the cause of the allergen. The power of the response relies upon the level of affectability and centralization of the antigen. The most probable diagnosis is neomycin induced contact dermatitis. The treatment of candidiasis is often challenging, with inadequate response to agents to treat the condition, reported in the literature. We report a case of a 24-yearold Indian male who presented with recurrent itching of glans and prepuce, dryness, peeling skin. After failing conventional treatment regimens, the patient received a trial of coconut oil with beclomethasone+clotrimazole cream. Complete resolution of cutaneous lesions reported after 2-3 days.
Keywords: Candidiasis; ICD; Neomycin; Mount test; Coconut oil.